Forkhead Box O-1 Modulation Improves Endothelial Insulin Resistance in Human Obesity - Karki, Shakun; Farb, Melissa G.; Ngo, Doan T.M.; Myers, Samantha; Puri, Vishwajeet; Hamburg, Naomi M.; Carmine, Brian; Hess, Donald T.; Gokce, Noyan (Arteriosclerosis, thrombosis, and vascular biology, 2015)
OBJECTIVE—Increased visceral adiposity has been closely linked to insulin resistance, endothelial dysfunction, and cardiometabolic disease in obesity, but pathophysiological mechanisms are poorly understood. We sought to investigate mechanisms of vascular insulin resistance by characterizing depot-specific insulin responses and gain evidence that altered functionality of transcription factor forkhead box O-1 (FOXO-1) may play an important role in obesity-related endothelial dysfunction. APPROACH AND RESULTS—We intraoperatively collected paired subcutaneous and visceral adipose tissue samples from 56 severely obese (body mass index, 43±7 kg/m) and 14 nonobese subjects during planned surgical operations, and characterized depot-specific insulin-mediated responses using Western blot and quantitative immunofluorescence techniques. Insulin signaling via phosphorylation of FOXO-1 and consequent endothelial nitric oxide synthase stimulation was selectively impaired in the visceral compared with subcutaneous adipose tissue and endothelial cells of obese subjects. In contrast, tissue actions of insulin were preserved in nonobese individuals. Pharmacological antagonism with AS1842856 and biological silencing using small interfering RNA–mediated FOXO-1 knockdown reversed insulin resistance and restored endothelial nitric oxide synthase activation in the obese. CONCLUSIONS—We observed profound endothelial insulin resistance in the visceral adipose tissue of obese humans which improved with FOXO-1 inhibition. FOXO-1 modulation may represent a novel therapeutic target to diminish vascular insulin resistance. In addition, characterization of endothelial insulin resistance in the adipose microenvironment may provide clues to mechanisms of systemic disease in human obesity.